THE EFFECT OF PROBLEM-BASED PRACTICE TOWARDS LEARNING OUTCOME AND PROCESS SKILL ON CELL MATERIAL - Viqi Novita; Meida Nugrahalia (Universitas Negeri Medan, 2020)
This study aims to determine the effect of problem-based practice on student learning outcome and process skill in cell material in class XI Science Kartika Private High School 1-2 T.P 2018/2019. This research was conducted in July-September, at SMA Kartika 1-2 Medan. The population of this study was all students of class XI as many as 179 people. Samples are taken randomly. There were as many as 72 students. Statistical analysis showed that the average student learning outcomes in the experimental class are pretest of 63.22 and posttest of 82.89, while the control class pretest is 59.55 and the posttest is 69.44. Then hypothesis test (t-test) showed that (tcount = 5.4561 > ttable = 1.997). Which is means that the problem-based practice has a significant effect on the learning outcome. Besides, practice using PBL models can improve student process skills. This is shown in the results of the experimental class observation sheet having an average process skill in the “High” category. Whereas in the control class the average process skill is only up to the “Medium” category. So it can be concluded that the Problem-based practice has a significant effect on the learning outcome and process skill of class XI students of Private Kartika Senior High School 1-2 Medan T.P 2018/2019.